Portable energy floor tiles - Goh, Guo Xian (2014)
The objective of this project is to create a proto-type portable energy floor tiles that harvest energy from a crowd during an event or carnival. The energy harvested will be stored in the tile and use to supply low electricity demands in the event. The project serves as a small effort towards green energy and saving the earth.